Desain Aplikasi Sistem Informasi Bimbingan Konseling Berbasis Web Di MAN 4 Jombang - lutvia nur khasanah; Izzatul Ummami; Lailia Rahmawati (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2022)
Abstract Information technology is currently developing very rapidly. One example and evidence of the development of information technology is school counseling guidance. MAN 4 Jombang is an educational school institution that still applies the manual method for recording student violations, with the manual method the reporting time takes quite a long time. The purpose of this study is to build a web-based Counseling Guidance (BK) information system that includes student data processing, attendance processing, and counseling data processing that will facilitate teacher staff (BK) in recording student violations. The design that will be used in this system uses the Waterfall model, by applying the Waterfall model because the resulting information system will be good, because it is made in stages so that it does not focus on a stage. This counseling guidance information system has five accesses, including admin, homeroom teacher, principal, counselor, and parents. An appropriate plan is needed for the solution to this problem, by building or designing a counseling guidance information system needed by the school.